Reduction and coordination properties of l-Lysine/l-arginine/l-cysteine for the improvement of the color of cured sausage. (15th May 2020) - Ning, Cheng; Bao, Pengqi; Zhang, Daojing; Li, Linxian; Chen, Li; Fang, Hongmei; Tang, Yuxiang; Zhou, Cunliu
Highlights: Lysine-/arginine-/cysteine-treatment caused visible absorbance at 544 and 582 nm. NO-treatment removed 544 and 582 nm absorbance but added absorbance at 536 and 570 nm. The 2550 cm −1 peak was eliminated with the cysteine treatment, regardless of NaNO2 /NO. EPR signal resulted from the cysteine treatment, regardless of NaNO2 /NO. The results facilitate meat industry applications for cured color improvement. Abstract: This study investigated how l -lysine/l -arginine/l -cysteine improved cured sausage color. Visible detection showed that Mb(Fe 2+ )NO did not form when MetMb(Fe 3+ ) was treated with a combination of l -lysine and NaNO2, l -arginine and NaNO2, or l -cysteine and NaNO2 . Visible spectra and electron paramagnetic resonance (EPR) detection together indicated formation of Mb(Fe 2+ )O2 when MetMb(Fe 3+ ) was treated with l -lysine, l -arginine, or l -cysteine; Mb(Fe 2+ )NO was formed when MetMb(Fe 3+ ) was treated with a combination of l -lysine and NO, l -arginine and NO, or l -cysteine and NO. Visible, EPR, and fourier transform infrared results suggested formation of a complex of Mb(Fe 2+ ) and l -cysteine by the coordination of sulfydryl and ferrous porphyrin. Therefore, l -lysine, l -arginine, or l -cysteine can promote the formation of Mb(Fe 2+ )NO by reducing MetMb(Fe 3+ ) to Mb(Fe 2+ )O2, and l -cysteine promotes formation of a complex of Mb(Fe 2+ ) and l -cysteine via coordination of sulfydryl and ferrous porphyrin, which may improve cured sausage color.